Mountain and holy wars - Davies, Tarandvd ([S.l.] : Wicklow Films (production company) ; [S.l.] : Journeyman Pictures, 2004)
This video covers the story about Imam Shamil and his guerilla tactic to free Chechnya from Russia. Russia labeled him as a terrorist but he is a hera to his people.
Executive producer, Donald Rosenfield
Keywords: Shamil, Imam, -- 1798?-1871; Muslims -- Russia (Federation) -- Caucasus Northern -- Political activity; Caucasus, Northern (Russia) -- History -- Autonomy and independence movements